Effects of steroid therapy in patients with severe fever with Thrombocytopenia syndrome: A multicenter clinical cohort study. - Sook In Jung; Ye Eun Kim; Na Ra Yun; Choon-Mee Kim; Dong-Min Kim; Mi Ah Han; Uh Jin Kim; Seong Eun Kim; Jieun Kim; Seong Yeol Ryu; Hyun Ah Kim; Jian Hur; et al. (Public Library of Science (PLoS), 2021)
Background Severe fever with thrombocytopenia syndrome (SFTS) is an acute, febrile, and potentially fatal tick-borne disease caused by the SFTS Phlebovirus. Here, we evaluated the effects of steroid therapy in Korean patients with SFTS. Methods A retrospective study was performed in a multicenter SFTS clinical cohort from 13 Korean university hospitals between 2013 and 2017. We performed survival analysis using propensity score matching of 142 patients with SFTS diagnosed by genetic or antibody tests. Results Overall fatality rate was 23.2%, with 39.7% among 58 patients who underwent steroid therapy. Complications were observed in 37/58 (63.8%) and 25/83 (30.1%) patients in the steroid and non-steroid groups, respectively (P < .001). Survival analysis after propensity score matching showed a significant difference in mean 30-day survival time between the non-steroid and steroid groups in patients with a mild condition [Acute Physiology and Chronic Health Evaluation II (APACHE II) score <14; 29.2 (95% CI 27.70-30.73] vs. 24.9 (95% CI 21.21-28.53], P = .022]. Survival times for the early steroid (≤5 days from the start of therapy after symptom onset), late steroid (>5 days), and non-steroid groups, were 18.4, 22.4, and 27.3 days, respectively (P = .005). Conclusions After steroid therapy, an increase in complications was observed among patients with SFTS. Steroid therapy should be used with caution, considering the possible negative effects of steroid therapy within 5 days of symptom onset or in patients with mild disease (APACHE II score <14).